Pemanfaatan Biochar Limbah Pertanian sebagai Pembenah Tanah untuk Perbaikan Kualitas Tanah dan Hasil Jagung di Lahan Kering - MATEUS, RUPA; KANTUR, DONATUS; MOY, LENNY M. (Agrotrop : Journal on Agriculture Science, 2018)
Utilization of Agricultural Biochar Waste as Soil Conditioner for Improved Soil Quality and Result of Corn in Dryland. Optimization of degraded dryland use need to be increased through by materials soil conditioner ground added, such as biochar which made from agricultural waste. Organic soil conditioner has been shown effective to accelerate the recovery of degraded drylands caused by conventional farming. This study aims to determine the effectiveness of biochar as a soil conditioner on the soil quality improvement and yield of corn in dryland as well. Research was carried out at State Agricultural Polytechnic field practice which is located in Oesao, East Kupang, Kupang regency, East Nusa Tenggara province. Design of this study was split plot factorial with three replications. The first factor as the main plot is kind of biochar, with four types, namely: Bs: biochar cow dung; Bp: rice husks; Bg: pruned G. sepium; and Bj: corn stover. The second factor as sub plots are doses of biochar, with three levels, namely: D1: 3 t ha-1; D2: 6 t ha-1; and D3: 9 t ha-1. The results showed that no interaction between the type and dose of biochar on soil quality and yield of corn. Each single factor either main plots and sub plot gave a significant difference on the quality of soil and yield of corn. Corn stover biochar and pruned G. sepium better improve soil quality and yield of corn in dryland than biochar that made from cow dung and rice husk. Doses tested biochar also showed different results and significantly improve of the soil quality and yield of corn.